Eklesiologi Bhinneka Tunggal Ika: Analisis Relasi Makna Semboyan Indonesia dengan Kategorisasi di Korintus - Kayla Nathania Thayeb; Gde Ngurah Reza Rizaldy (Kharisma: Jurnal Ilmiah Teologi, 2023)
Abstract Contextual theology is a valuable step in being able to present the gospel within a culturally diverse frame of mind. Of course as Indonesians, local culture can be one of the tools in doing so, such as having a dialogue on the concept of unity in Corinth with the motto of the Indonesian nation. This step is intended to look at the social background and writing context attached to the text, as well as the essential values where there are similarities or differences between the text and the concept of Indonesian culture. As a result of the analysis, researchers see differences and similarities that complement each other, where the concept of Bhinneka Tunggal Ika which celebrates differences in unity can become a concept of church life in Indonesia. Abstrak Teologi kontekstual merupakan langkah yang berharga untuk dapat menyajikan injil dalam kerangka berpikir kultur yang beragam. Tentu sebagai orang Indonesia, kultur setempat dapat menjadi salah satu alat dalam melakukannya, seperti mendialogkan konsep persatuan dalam Korintus dengan semboyan bangsa Indonesia. Langkah tersebut dimaksudkan untuk melihat latar belakang sosial dan konteks penulisan yang melekat pada teks, serta nilai esensial dimana terdapat kesamaan pun perbedaan teks dengan konsep kultur Indonesia. Sebagai hasil analisis, peneliti melihat perbedaan dan persamaan yang saling mengisi, dimana konsep Bhinneka Tunggal Ika yang merayakan perbedaan dalam kesatuan dapat menjadi konsep hidup menggereja di Indonesia.